WORKING WITH A DYSFUNCTIONAL FAMILY IN THE SOCIAL ASSISTANCE SYSTEM IN POLAND - Beiger, Galina (Mountain School of Ukrainian Carpaty, 2019)
Dysfunctional families are families that fail to fulfill the protective and educational function of their children. They are conflicted, affected by addictions, unadapted to life, inefficient in education. The situation of these families is a challenge for the Polish social assistance system. As part of social work with these families, a number of different methods are used, among others empowerment, interdisciplinary work model, work with family assistants, psychological therapies, school for parents, Family Group Conference and day support facilities. The work methods used involve family members based on their resources and aim to ensure that families use their strengths and acquire appropriate care and upbringing skills, achieve balance and gain greater independence in functioning, and regain control over their own lives. Сhanges that take place in social life cause weakening of social ties and the role of the family as a basic environment of human upbringing. Many Polish families are unable to perform the protective, educational, economic, preventative functions of their members, including children. Particularly disadvantaged families - affected by addictions, illnesses, disorders, unadapted to life and ineffective in education - pose a serious threat to the development of children, but also a great challenge for the social assistance system. For many years, social assistance institutions have usually been a source of financial resources to support these families. The current development of the family support system tends to develop effective methods of working with families, these pedagogical tools can be used by social workers and family assistants. Their essence is to influence the restoration of relationships between family members, the improvement of relations and communication, the desire for family reintegration. To this end, actions are taken based on the developed procedures based on the resources inherent in the family to make changes in the functioning of the family system through the forces of its members. The effectiveness of social work with disadvantaged families is enhanced by interdisciplinary activities that involve the use of the knowledge, experience and professional skills of various institutions and non-governmental organizations. Nowadays, the best way to work with such a family is to involve the so-called human factor, which embodies the professionalism and effectiveness of the assistance provided. A crisis family is increasingly perceived as an entity responsible for their own destiny. Working with the family using the above mentioned methods takes into account not only the deficiency of its functioning, but above all its strengths and potentials, which allows it to gradually regain balance, stability and take control of their life.